Entwicklung eines druckgetriebenen dynamischen Kolonnenmodells zur Erhöhung der Flexibilität von kryogenen Luftzerlegungsanlagen - Wunderlich, Bernd (KIT Scientific Publishing, 2018)
Driven by market signals, energy consumers are motivated to adapt their grid load. Due to their cryogenic storage capacity, air separation units can efficiently be used for load shifting. Such an operation leads to new challenges for plant operation and control. The developed pressure-driven dynamic column model is used to investigate load-flexible operation.